(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2012)
Introduction : Erythema Nodosum Leprosum is the chronic recurrent systemic complication of multi-bacillary leprosy particularly Lepromatous Lepromatous Leprosy and Borderline Lepromatous Leprosy. It is frequently associated with the development of neuritis, iritis, orchitis, arthritis / dactylitis of hands and feet, etc. Decades ago, it was well managed with thalidomide but now a high dose of Clofazimine and Steroid are the recommended drugs by the World Health Organization. Unfortunately there are some patients who do not respond to this regimen or experience relapse after they attempt ot reduce their steroid below 15-20mg / day. Objective : We undertook this study to find out an effective and safe treatment regimen for those resistant patients. Methodology : During 2007-2011, we treated 9 resistant ENL patients. They were ENL reaction with (a) Skin Ulcers-2, (b) Neuritis-2, (c) Nerve Abscess-1, (d) Iritis-1, 9e) Orchitis-2 and (f)Arthritis/Dactylitis-1. All had comparable clinical and bacteriological features and almost similar history of incomplete response to courses of conventional treatment in hospital, during last 1-1 1/2 years. We treated them all with a combination of Methotrexate and Predinisolone for 21/2 -31/2 years. Results : We observed smooth remission of ENL-reaction in all our patients. No remarkable side effects were seen in our patients, except mild weight gain in one, weight gain and facial swelling in one, two attacks of multiple folliculitis and one attack of extensive P. versicolor in another one and Norwegian scabies in one. Conclusion : A combination of low dose Prednisolone and Methotrexate was found safe and effective in managing resistant ENL reaction and we welcome controlled study in this regard. JCMCTA 2011; 22(2): 44-46